Hydropedological behavior of a chromic vertisol under different plant covers - Villazón-Gómez, Juan Alejandro (Revista de Ciencias Agrícolas, 2021)
Vertisols present edaphic limiting factors primarily of a physical nature. The study of their hydropedology, supported by multivariate techniques, is of vital importance. The work was developed with the objective of determining, through multivariate analysis, the hydropedological behavior of a Chromic Vertisol under different plant covers. In areas under natural grass, sugarcane, and secondary forest, belonging to the Holguín Sugarcane Provincial Research Station, three random points were chosen in each. Soil penetration resistance, soil bulk density, gravimetric moisture, and volumetric moisture at depths of 0-10, 10-20 and 20-30cm were determined. A Principal Component Analysis and Canonical Correlations were performed using Statistica 7 and Statgraphics Plus XV.II. The first two components made the greatest contribution to the variance, with 83.09%. The greatest contributions (1st component) were given by moisture at all depths and by soil compaction at a depth of 20-30 cm. The 2nd component was influenced by soil compaction in the 0-10 and 10-20cm layers. There was a contrast between the variables that characterize the solid phase with which they describe the liquid phase of the soil. There was a correlation between soil moisture and compaction. The first two pairs of canonical variables showed a strong linear correlation and regularly dispersed along the central values of the model, with a remarkable grouping by depths.